Unpacking Economic Uncertainty — Measuring the Firm, Sector and Aggregate Components - Siavash Mohades; Giulia Piccillo; Tania Treibich (Center for Economic Studies and ifo Institute (CESifo), 2024)
We introduce a novel method for measuring economic uncertainty at the firm, sector, and aggregate levels using sales volatility and validate it by comparison with existing macroeconomic uncertainty measures. We use Compustat firms data in the period 2000-2022 to construct our uncertainty measures for the U.S. economy. Our findings highlight that 1) macroeconomic conditions are the predominant source of firms' uncertainty, 2) diverse firm traits yield notable heterogeneity, and 3) the manufacturing sector exhibits the highest uncertainty among sectors. Our findings shed light on the importance of firm and sectoral heterogeneity in studying uncertainty and its effects on economic activity.
Keywords: D80; D22; E32; L11; L25; 330; measuring uncertainty; firm heterogeneity; balance sheet data; business fluctuations